0337 Modelling of occupational exposure to inhalable nickel. (21st August 2017) - Kendzia, Benjamin; Pesch, Beate; Koppisch, Dorothea; Gelder, Rainer Van; Pitzke, Katrin; Zschiesche, Wolfgang; Weiss, Tobias; Behrens, Thomas; Brüning, Thomas
Abstract : Objectives: Exposure to nickel (Ni) is widely distributed in the production and processing of steel or alloys. We compiled concentrations of inhalable Ni together with information about the duration of the measurement, analytical method, and workplace characteristics in the MEGA database. Methods: This analysis was based on 8052 personal measurements of inhalable Ni collected between 1990 and 2009. Mixed-effects models were applied to the log-transformed Ni concentrations with imputed non-detects to assess the geometric means (GMs) of exposure to Ni in the various occupational settings adjusted by duration of sampling and calendar year. Results: Most of measurements (38%) were collected in welders, which we further detailed by welding technique. Major predictor of the concentration was the technique and material in welding-related tasks. Highest exposure levels were estimated for welding materials of high Ni content with gas metal arc welding (48 μg/m 3 ; 95% CI 32–72 μg/m 3 ) and shielded metal arc welding (37 μg/m 3 ; 95% CI 24–57 μg/m 3 ). Furthermore, high GMs were estimated in metal sprayers (33 μg/m 3 ), in the manufacture of batteries (27 μg/m 3 ) and in forging-press operators (25 μg/m 3 ). We did not observe time trends of exposure to Ni in this period. Conclusion: Ni concentrations varied considerably between occupations and were influenced by process and Ni content of consumables in welders. In order to assess exposure to Ni in community-based studies, supplemental information on job tasks, processes and materials is essential in addition to job titles.